The role of the ruling authorities in securing trade and Hajj routes in the Central Maghreb (6-10 AH/12-16 AD) - Agouni, Ayoub; gueriane, adjalil (The Algerian Historical Journal, 2026)
Scrutinizing the topic of the efforts of the ruling authority in securing the trade and pilgrimage routes in the countries of the Central Maghreb is a historical study that requires the researcher to extrapolate various historical texts which can provide information in regards to the efforts and positions of the ruling political authorities in securing the trade and pilgrimage routes of the caravans of the countries of the Central Maghreb.After following and reading the texts, the researcher came to the conclusion that the ruling political authorities in the countries of the Central Maghreb worked to stop the activity of thieves and bandits and mitigate their effects, and monitor the necessary preventive measures and restraints concerning imposing security on the roads to confront those who violate it, such as thieves, warriors and bandits, and their actions were reflected in a fruitful way for the economy and society, ceasing the aggressors’ malicious behaviour and lessening their impact.